(untitled) (The Review of Diabetic Studies, 2024)
The digital transformation of healthcare systems represents a paradigm shift in service delivery, particularly within emergency medical services and hospital operations. This systematic review examines the integration of artificial intelligence-enabled dispatch systems, workforce optimization strategies, and integrated care pathways within the Saudi Arabian healthcare context. A comprehensive search of PubMed, Scopus, and Web of Science databases identified 47 studies meeting inclusion criteria for analysis. Findings reveal that AI-enabled dispatch systems demonstrate significant potential for reducing response times and improving triage accuracy, while workforce optimization algorithms can enhance staff allocation efficiency by 15-30%. Integrated care pathways supported by digital infrastructure show promise in reducing hospital length of stay and improving continuity of care. However, implementation barriers including interoperability challenges, workforce readiness, and data governance frameworks remain substantial in the Saudi context. The review identifies critical gaps in empirical evidence specific to Middle Eastern healthcare systems and highlights the need for culturally adapted implementation frameworks. These findings have direct implications for healthcare administrators and policymakers pursuing Vision 2030 objectives for digital health transformation in Saudi Arabia.